Sustainable Employability, Organizational Identification, and Psychological Empowerment: A Moderation Mediation Model Test - Cahyani, Intan Sukma; Ekowati, Dian (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study examines the relationship of psychological empowerment and organizational identification to sustainable employability with work engagement as a mediator variable and affective commitment as a moderator variable in financial cluster state-owned enterprises (SOE) employees. Design/Methods/Approach: This research utilized Structural Equation Modeling (SEM) with 220 respondents. Data was gathered through open-ended questionnaires from employees in the financial sector of state-owned enterprises. Findings: The findings of this study indicate that psychological empowerment and work engagement have a notable and favorable impact on sustainable employability. However, they do not have a significant effect on organizational identification. It is worth noting that organizational identification does have a large and positive influence on work engagement. Work engagement does not act as a mediator in the connection between organizational identification and sustainable employability. However, it does serve as a mediator in the association between psychological empowerment and sustainable employability. Affective commitment enhances the strong and favorable correlation between work engagement and sustainable employability. Originality/Value: The field of sustainable employability is under-researched, leading to a lack of consistency in addressing its multifaceted issues and a scarcity of theoretical frameworks. This study aims to consolidate disparate research by integrating various variables and examining their interplay through mediating and moderating mechanisms informed by the Job Demand-Resource Theory and Social Identity Theory. Practical/Policy implication: It is imperative for organizations to prioritize the cultivation of robust and morally upright leadership across all levels, particularly at the upper echelons where executive management holds sway over the direction of the enterprise. In the immediate context, fostering a sense of identification among employees with the organizational ethos is crucial. Over the long term, such efforts contribute to the holistic well-being of employees, encompassing both physical and psychosocial dimensions, thereby fostering sustainable employability.